Pedagogical, Psychological and Psychotherapeutic Help in Overcoming Learning Difficulties to Facilitate Development (Revue internationale du CRIRES : innover dans la tradition de Vygotsky, 2017)
The paper discusses theoretical basics for organising the work and interaction of di˙erent specialists helping children with learning diÿculties (teachers, counsellors, therapists). The multivector model of the zone of proximal development based on cultural-historical psychology and developed in the theoretical framework of Reﬂection-Activity approach is proposed as such basic value. We connect di˙erent types of help to various developmen-tal vectors and regard them as technologies to enhancing the client’s development. We reveal the contents of such notions as cooperation, zone of proximal development, agency, reﬂection, and problem’s epicentre. We present di˙erent ways of operationalizing these notions applied to aiding children with learning diÿculties. The notion of dual resource we propose is important for developing new techniques of working in the zone of proximal development; it is this basis certain technologies of organising the client’s reﬂection are relying on. We give examples of counselling children in such way and present a com-parative analysis of the counsellor’s work with action schemas and cognitive-behavioural therapist’s work with problematic emotional states and behaviours in children with learn-ing diÿculties. The theoretic system we disclose helps to comprehend the famous quote from Lev Vygotsky: “one step in learning may signify a hundred steps in development”.
Keywords: Cultural-historical psychology; Development; Learning; Help in overcoming learning difficulties; Pedagogics; Psychological counselling; Cognitive-behavioural therapy; Reflective-activity approach; Multivector model of the zone of proximal development; Position of agency; Reflection; Dual resource; Problem’s epicenter